2016
DOI: 10.5539/gjhs.v8n12p206
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Social Support in Mothers with β-Thalassemia Children

Abstract: Background: In our knowledge, there was no available information on social support and caregiver's burden among parents of thalassemic children. Aim:To examine caregiver's burden and social support in mothers of thalassemic children, this study was conducted. Methods:This cross-sectional study was conducted from July to October 2013 in Jiroft Thalassemic Center (JTC) in southeast of Iran. To assess the caregiver's burden and social support, caregiver burden scale and Norbeck social support questionnaire was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
0
21
1
1
Order By: Relevance
“…All participants hoped for their children to get married, continue education, find a job and become independent in future. Parents in Previous studies have similar concerns about their children [27,33] Concern about children's marriages was not reported in some studies conducted in other countries [10] . This concern reflects the importance of marriage in the Iranian/Islamic culture.…”
Section: Uncertainty About Futurementioning
confidence: 91%
See 2 more Smart Citations
“…All participants hoped for their children to get married, continue education, find a job and become independent in future. Parents in Previous studies have similar concerns about their children [27,33] Concern about children's marriages was not reported in some studies conducted in other countries [10] . This concern reflects the importance of marriage in the Iranian/Islamic culture.…”
Section: Uncertainty About Futurementioning
confidence: 91%
“…Widayanti stated that parents of children with thalassemia suffer tremendously from provision of daily life-long care for their child [26]. Also Mashayekhi et al reported that psychological problems annoyed families more than other problems [27]. Also Liem et al reported feelings of concern and despair experienced by these parents [28].…”
Section: Immersion In Sufferingmentioning
confidence: 99%
See 1 more Smart Citation
“…The improper coping behaviors of the parents result in unfavorable effects on managing the disease of their children and following the treatments (35). The people in charge and nurses should help the parents to enhance their management ability by consultations and administration of suitable interventions (10,36).…”
Section: Discussionmentioning
confidence: 99%
“…The hereditary nature of this disease, changes in appearance, expecting early death, and need for continuous treatment, impose unfavorable psychological impacts on patients and their families (10,11). Patients with thalassemia are prone to various psychological disorders (12,13).…”
Section: Introductionmentioning
confidence: 99%